Development of Teaching Materials for a Catholic Marriage Preparation Course for Prospective Married Couples - Gunawan, Gunawan (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This research uses a qualitative approach to explore the implementation of the Catholic Marriage Preparation Course at St. Teresia Jambi. With a focus on in-depth understanding, the research aims to identify and resolve the fundamental problems faced by course organizers. The research subjects consisted of a group of companions and participants in the Catholic marriage preparation course at St.Teresia Jambi. Data was collected through direct interviews and questionnaires, then analyzed using qualitative analysis techniques. The results of the research show that there is an urgent need for increased understanding and deepening of the teachings of the Catholic Church related to marriage preparation and formation at St. Mary's Parish. Teresia Jambi. Apart from that, the research results also reveal that the application of Catholic marriage principles which are in line with Church teachings can strengthen family ties and improve the spiritual well-being of the people. The novelty of this research lies in the qualitative approach used to gain an in-depth understanding of the problems of Catholic marriage preparation courses. It is hoped that the implications of this research will provide valuable input for course organizers in improving the quality and effectiveness of Catholic marriage preparation courses at St. Mary's Parish. Mary. Teresia Jambi.